2019
DOI: 10.24176/kredo.v3i1.3865
|View full text |Cite
|
Sign up to set email alerts
|

Semantics Analysis of Slang (SAOS) in Social Media of Millennial Generation

Abstract: Generation were born in every era eventually create their own language not least the latest generation commonly called the millennial generation. Specifically, the aim of our work broadens current knowledge of the phenomenon of Semantics Analysis of Slang (SAOS) in Social Media of Millennial Generation. This study investigated: 1) the types of SAOS used by millennial generation in social media; 2) how the meaning of SAOS used by millennial generation in social media; 3) why millennial generation used SAOS in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 1 publication
(1 reference statement)
1
30
0
1
Order By: Relevance
“…Umumnya pengaruh Bahasa Inggris dalam bahasa anak muda di berbagai negara dan wilayah, lebih banyak dikaji dari pendekatan semantik (Matsumoto et al 2011;Rezeki and Sagala 2019; Slotta 2016). Dapat dipertimbangkan yang dapat menjadi alas an kecenderungan ini adalah karena karakteristik bahasa anak muda sendiri yang sulit dimengerti sehingga multitafsir dan menarik untuk dikaji dari kajian semantic.…”
Section: C)unclassified
“…Umumnya pengaruh Bahasa Inggris dalam bahasa anak muda di berbagai negara dan wilayah, lebih banyak dikaji dari pendekatan semantik (Matsumoto et al 2011;Rezeki and Sagala 2019; Slotta 2016). Dapat dipertimbangkan yang dapat menjadi alas an kecenderungan ini adalah karena karakteristik bahasa anak muda sendiri yang sulit dimengerti sehingga multitafsir dan menarik untuk dikaji dari kajian semantic.…”
Section: C)unclassified
“…On average, a new generation emerges every 20 years and each generation has different desires, needs and actions. Each generation has unique gaze identity structures (Stark and Poppler, 2018; Rezeki and Sagala, 2019). This is the basis of generational conflict and differences in understanding among people working together in organizations.…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…When these generations that dominate business life are listed chronologically, the traditional generation (1927–1945), the baby boom generation (1946–1964), the X generation (1965–1980), the Y generation 1980–2000 (Castellano, 2013; Breker et al , 2018). The footsteps of the Z generation, who were born at the beginning of 2000 and started to take part in business life in a short time, are heard today (Keengwe and Agamba, 2015; Rezeki and Sagala, 2019). Generation Y, which is the subject of this research, is a mobile generation that, unlike previous generations, grew up in the era of technological innovation dominated by computer technology.…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Benany (2020), the research found that from four types of slang words in terms, there are three types of slang words applied by the members of keluarga besar group whatsapp. Rezeki & Sagala (2019), the research showed that millennial generation used slang words in their communication in social media namely 33 slang words in Facebook and 31 slang words in Instagram. Suhardianto (2016), the results of the research found that construction of slang can be seen from seven ways, abbreviation, deletion, letter and sound change, adoption of basic word, mixed abbreviation, citation, new construction.…”
Section: Introductionmentioning
confidence: 99%